Development and validation of a food literacy instrument for school children in a Danish context. (1st January 2021) - Stjernqvist, Nanna Wurr; Elsborg, Peter; Ljungmann, Cecilie Karen; Benn, Jette; Bonde, Ane Høstgaard
Abstract: Food literacy (FL) is an aim of food education and cooking interventions, but is defined and measured in different ways. In this study we developed, tested, and validated a FL instrument targeting children aged 12–14 years that builds on a broad 5-dimensional FL concept that includes the competencies of knowing and doing, as well as the rarely investigated competencies of using the senses, caring for others, and wanting to participate as a citizen regarding food issues. The study had 3 phases: 1) item development involving an expert panel; 2) scale testing comprising a face validity test with 12 pupils and a test with 817 pupils, of which 267 took part in a retest; and 3) scale validation including testing dimensionality by confirmatory factor analysis (CFA), internal reliability by Cronbach α, external reliability by intraclass coefficient (ICC), and convergent and predictive validity by regression analysis. CFA showed an acceptable model fit, confirming the concept of FL as 1 factor and its 5 distinct competencies as subfactors. There was good internal reliability for total FL score (α = 0.85) and good external test–retest reliability (ICC = 0.92). Convergent validity for a similar health literacy construct was significant for the total FL scale and its 5 competencies; this was also true for the predictive validity of FL with food intake as an outcome. This 37-item, 5-dimensional FL instrument can be used to assess FL levels in children and can guide food and nutrition education.